Cost-effectiveness and budget impact of covering Burkitt lymphoma in children under Ghana’s National Health Insurance Scheme - Richmond Owusu; Dakota Pritchard; Lieke Fleur Heupink; Godwin Gulbi; Brian Asare; Ivy Amankwah; Joycelyn Azeez; Martha Gyansa-Lutterodt; Lydia Dsane-Selby; Ruby Aileen Mensah; William Omane-Adjekum; Francis Ruiz; et al. (Cost Effectiveness and Resource Allocation)
Abstract Background Childhood cancer is not a high priority in health care financing for many countries, including in Ghana. Delayed care seeking and treatment abandonment, often due to the financial burden of care seeking to families, are common reasons for a relatively low overall survival (OS) in low-and middle-income countries. In this study, we analyzed the cost-effectiveness of extending health insurance coverage to children with Burkitt lymphoma (BL) in Ghana. Methods We developed a Markov model in Microsoft Excel to estimate the costs and effects of BL treatment when National Health Insurance Scheme (NHIS) was provided compared to the status quo where NHIS does not cover care for childhood cancer. The analysis was undertaken from the societal and health system (payer) perspective. Both costs (measured in $) and effects, measured using disability adjusted life years (DALYs), were discounted at a rate of 3%. The time horizon was a lifetime. Probabilistic sensitivity analysis was done to assess uncertainty in the measurement of the incremental cost-effectiveness ratio (ICER). A budget impact analysis was undertaken from the perspective of the NHIS. Results In the base-case analysis, the intervention (NHIS reimbursed treatment) was less costly than current practice ($8,302 vs $9,558). The intervention was also more effective with less DALYs per patient than the standard of care (17.6 vs 23.33). The ICER was -$219 per DALY averted from societal perspective and $113 per DALY averted from health system perspective. The probabilistic sensitivity analysis showed that the intervention is likely to be both less costly and more effective than current practice in 100% of the 1,000 simulations undertaken. Conclusion Providing health insurance coverage to children with BL is potentially cost-effective. The effectiveness and cost-savings relating to this strategy is driven by its positive impact on treatment initiation and retention. Based on this evidence, there has been a policy change where Ghana’s NHIS has prioritized financing for cancer treatment in children.